Desenvolvimento econômico e a produção do território no Brasil: as promessas do territorialismo competitivo - Weslley Antonio Tadeu Monteiro Cantelmo (2014)
This study aims to discuss the production of territory in Brazil, for which category of analysis is the concept of development and its influence upon hegemonic practices in Brazilian society. The historical and geographical processes of Brazilian societys development were driven by promises of inclusion in modernity. The concept of development, unfolded from the idea of progress, was a social fuel which supplied this move of capitalist relations in Brazil in the 20th century. Therefore, the dominant idea of rulers has generally been the inclusion of Brazilian regions in the circuit of capitalist competition. Nevertheless, the process showed several distortions from which arose political resistance movements in favor of better planned territorial production perspectives as opposed to those formerly theoretically provided, i.e. developmental capitalism. Thus this study means to identify the elements of a dialectical movement between territorial production based on logical principles of development and other forms, contrary to this principle. It was then verified that the developmental conception has been enhanced in Brazilian social domain, under the influence of its elites, with strategies based on reproduction, which stress the discourse in favor of production of competing territories.